The Impact of Soft Skills Training on the Behavior of Multinational Technology Company Employees - Annie Wong Pooi Hang; Tarika Singh Sikarwar; Nor Alia Balqis Nordin; Norakma Irwany Rosley; Noureysha Mudzaffar; Nur Adriana Sofea Shokri; Neha Patel; Kee Daisy Mui Hung (AIBPM Publisher, 2024)
This research aims to evaluate the impact of soft skills training on the behaviour of multinational technology company employees - Intel Corporation. A survey questionnaire was designed to gather quantitative data regarding the employees' experiences with soft skills training at Intel Corporation Malaysia, covering various dimensions of communication, leadership, teamwork, and conflict resolution in the data collection. A sample of 150 employees of Intel Corporation in Malaysia responded to the study, providing diverse perspectives on how soft skills training can impact employees’ behavior. The data analysis employed both descriptive and inferential statistics, including correlational and regression analyses. The results indicated that soft skills training significantly enhances employee cooperation, leadership acumen, and communication proficiency. The findings have significant implications for Intel Corporation. Enhanced interpersonal skills from such training contribute to better conflict resolution, improved collaboration, and increased employee satisfaction, ultimately boosting productivity and reducing turnover rates. In conclusion, the study underscores the necessity for continuous investment in soft skills training to cultivate a resilient and adaptive workforce, thereby ensuring sustained organizational success and competitive advantage.